The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep38500
|View full text |Cite
|
Sign up to set email alerts
|

An increased duplication of ZRS region that caused more than one supernumerary digits preaxial polydactyly in a large Chinese family

Abstract: Preaxial polydactyly (PPD) is inherited in an autosomal dominant fashion and characterized by the presence of one or more supernumerary digits on the thumb side. It had been identified that point mutation or genomic duplications of the long-range limb-specific cis-regulator - zone of polarizing activity regulatory sequence (ZRS) cause PPD or other limb deformities such as syndactyly type IV (SD4) and Triphalangeal thumb-polysyndactyly syndrome (TPTPS). Most previously reported cases involved with no more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…When it occurs in isolation, autosomal dominant variations in a single gene are typically involved. 6 Genetic variants in the zone of polarizing activity regulatory sequence (ZRS, OMIM 605522), a limb-specific cis-regulator located in intron 5 of the LMBR1 on chromosome 7q36, have been linked to most PPD types, including PPD II, PPD II/III, triphalangeal thumb-polysyndactyly syndrome (TPTPS, OMIM 188770), syndactyly type IV (SD4, OMIM 186200), and Werner mesomelic syndrome (WMS, OMIM 188770), [7][8][9][10][11][12] indicating that variants at ZRS can lead to different PPD phenotypes. In this region, more than 20 point variants, 10 duplications, 1 triplication, and a base pair insertion have been reported to be associated with PPD.…”
Section: Introductionmentioning
confidence: 99%
“…When it occurs in isolation, autosomal dominant variations in a single gene are typically involved. 6 Genetic variants in the zone of polarizing activity regulatory sequence (ZRS, OMIM 605522), a limb-specific cis-regulator located in intron 5 of the LMBR1 on chromosome 7q36, have been linked to most PPD types, including PPD II, PPD II/III, triphalangeal thumb-polysyndactyly syndrome (TPTPS, OMIM 188770), syndactyly type IV (SD4, OMIM 186200), and Werner mesomelic syndrome (WMS, OMIM 188770), [7][8][9][10][11][12] indicating that variants at ZRS can lead to different PPD phenotypes. In this region, more than 20 point variants, 10 duplications, 1 triplication, and a base pair insertion have been reported to be associated with PPD.…”
Section: Introductionmentioning
confidence: 99%
“…Preaxial polydactyly is the most common duplication in Caucasian and Asian populations, and it occurs in 0.8–1.4 cases per 1000 births [ 1 ]. Abnormal expression of morphogens, such as Hox genes, bone morphogenic proteins, LMBR1, Gli-3, and increased duplication of ZRS region has been associated with thumb duplication [ 2 5 ].The Wassel system, which was developed in 1969, has become the universal classification system for thumb duplication due to its simplicity [ 1 ]. Type IV thumb duplication is the most common type, and it is followed by type II and then type VII [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The sonic hedgehog (Shh) signaling pathway is essential for regulating digit number and identity [ 16 19 ]. Mutations or genomic duplications in the zone of polarizing activity regulatory sequence (ZRS), a long-range limb-specific cis-regulator of Shh have been widely reported to cause preaxial polydactyly in humans [ 6 , 7 , 20 22 ]. Similarly, QTL mapping and GWA studies showed that the chicken polydactyly mutation was linked to the chromosome 2p region [ 3 , 4 , 23 25 ].…”
Section: Introductionmentioning
confidence: 99%